EFFECT OF EMPLOYEE LABOR EXPENSES ON THE RESPONSE TIME IN EMERGENCY DEPARTMENT OF SAMPANG HOSPITAL, INDONESIA - Miftahul Khoirul Insan; Prananda Surya Airlangga; Lilik Djuari (Universitas Airlangga, Surabaya, Indonesia, 2021)
Background: The Emergency Department (ED) has the main purpose of receiving, triageing, stabilizing, and providing acute health services to patients, including those who require resuscitation and emergency patients to some degree. An indicator of the success of medical treatment of emergency patients is the speed of providing adequate assistance both in daily routine situations or during disasters. Factors that influence nurses’ motivation to work, especially implementing triage at the Emergency Department include the characteristics of nurses such as age, sex, education, length of work and training. Objective: To analyze the effect of workload of the medical staff of the Emergency Department on the response time in the Emergency Department of Sampang Hospital, Indonesia. Materials and Methods: Observational analytic research with cross-sectional design. Sampling was performed with total sampling method to 24 people who met the criteria. Data collection was done by questionnaire and observation. Data were analyzed using the Chi-square correlation test and Fisher’s exact test. Results: There was a significant influence between workload and response time of triage P1 of Emergency Department staff at Sampang Hospital, Indonesia (p=0.015), whereas in triage P2 and P3 there was no effect of workload of staff on response time (p>0.05). Conclusion: In Emergency Department of Sampang Hospital, Indonesia, the response time in all categories of emergency (P1/red, P2/yellow, and P3/green) is fast. Workload correlates significantly with response time in P1/red category, while in P2/yellow and P3/green categories the workload has no effect on the response time.